Homologous specialization of arcuate fasciculus ventrolateral frontal connectivity in marmosets and humans - Yufan Wang; Luqi Cheng; Deying Li; Yuheng Lu; William D. Hopkins; Chet C. Sherwood; Ting Xu; Cirong Liu; George Paxinos; Tianzi Jiang; Congying Chu; Lingzhong Fan (Proceedings of the National Academy of Sciences, 2026)
The arcuate fasciculus (af) is a crucial dorsal pathway underpinning human language, yet its weak frontal connectivity in macaques—the standard primate model—creates an evolutionary puzzle. Here, we investigate the common marmoset, a distantly related platyrrhine with high vocal complexity, to test for convergent neural adaptations. By integrating retrograde and anterograde tracing with ultra-high-resolution diffusion MRI, we identified a robust af homolog in marmosets that is anatomically distinct from the superior longitudinal fasciculus. Comparative mapping across marmosets, macaques, chimpanzees, and humans reveals a notable similarity in connectivity patterns: The marmoset af terminates extensively in the ventrolateral frontal cortex, exhibiting a connectivity profile significantly more similar to humans than to that of the phylogenetically closer macaque. Functionally, this pathway targets cortical regions activated during vocal exchanges, partially overlapping with the human speech network. These findings suggest that the frontal connectivity of the dorsal audio-motor pathway is not strictly determined by phylogenetic proximity but represents an evolutionarily labile scaffold that undergoes lineage-specific elaboration under pressure associated with complex vocal communication.